Magsår hos gris : förekomst och faktorer som påverkar - Nyman, Camilla (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2010)
Gastric ulcer is a common disease among pigs in the whole world where an intensive production occurs. It is mainly the upper region, the nonglandular region of the stomach that is affected. Gastric ulceration is a disease with several risk factors. The factor that seems to have the largest impact on the development of gastric ulceration is a small particle size of the feed. The reported prevalence of gastric ulceration differs from 5 to 100 % and it is a large herd-to-herd variation. Gastric ulcer is a disease that is hard to detect on the live animal because the symptoms are difficult to interpret. It is not unusual to find healthy looking pig that sudden die due to gastric ulcer. Some factors that have a positive impact on growth and fed efficiency have a negative impact on the development of lesions and gastric ulceration in the nonglandular region of the stomach. This relationship makes the prevalence of gastric ulcer to be a problem that remains.